Estimation of salivary and serum basic fibroblast growth factor in treated and untreated patients with oral squamous cell carcinoma - Archana Gupta; Anurag Tripathi; Ranjitkumar Patil; Vijay Kumar; Vikram Khanna; Vandana Singh (Elsevier, 2019)
Objective: The purpose of this study was to evaluate salivary and serum basic fibroblast growth factor (bFGF) level in OSCC patients to provide a reliable biomarker for the early detection, monitoring, and prognosis of OSCC patients. Materials and methods: The study enrolled 90 subjects, equally grouped as recently diagnosed & untreated OSCC patients (Group I), treated OSCC without any recurrence (Group II) & as control (Group III). Enzyme-linked immunosorbent assay was employed to measure bFGF concentrations in saliva and serum samples of all three groups. The results were tabulated and analyzed statistically. Results: Group I showed high-level of bFGF expression profile in saliva (8.80 ± 1.26 pg/ml) whereas the levels of bFGF in group II (2.69 ± 0.17 pg/ml) and Group III (3.17 ± 0.43 pg/ml) are significantly lower than group I. Serum bFGF levels were also high in group I (6.33 ± 0.81 pg/ml) and decreased significantly in group II (3.52 ± 0.45 pg/ml) however, the control group showed elevated range of levels (7.63 ± 0.88 pg/ml). Conclusions: This study demonstrates the reliability of salivary bFGF marker as diagnostic as well as prognostic marker. Serum bFGF could also be used as prognostic marker only in Oral Squamous cell carcinoma patients.